Infant and Young Child Feeding Practices and Their Association with Women's Autonomy: A Community-Based Study in Rural West Bengal - Najir Hosen Sarkar; Kuntala Ray; Subhra Samujjwal Basu; Kalpana Gupta; Mamunur Rashid; Mausumi Basu (Healthline)
Introduction: In majority of societies women are the primary caregivers of children. Poor feeding habits in early childhood contribute to malnutrition and child mortality in India. While the effects of some of the resources such as education on child feeding practices have been extensively evaluated, women's autonomy have received less attention. Objective: To assess feeding practices among the infants and young children in Budge-budge II block of West Bengal. Method: Adescriptive study with cross-sectional design was conducted among 161 children between 6-23 months of age and their respondent mothers in Budge-Budge II block, West Bengal, using multistage random sampling. Mothers were interviewed face to face, and data were collected using a predesigned, pretested and structured IYCF practice schedule and a Likert-type women's autonomy measurement scale and analysed using SPSS v26.0. Multivariable binary logistic regression and the Pearson's correlation was done to find association. Results:Among the study participants, 155 (96.3%) reported being breastfed, 29 (18%) received pre-lacteal feed, 60 (37.3%) had not initiated breastfeeding early within 1 hour, 149 (92.5%) received colostrum, 39 (24.2%) were not exclusively breastfed; 119 (73.9%) of the study participants had adequate meal frequency whereas 87 (54%) and 97 (60.2%) had inadequate dietary diversity and acceptable diet respectively. Overall IYCF practice was significantly poor 113 (70.2%). Among the mothers 88 (54.7%) had lower level of autonomy. Conclusion: More than half of the study participants had poor overall IYCF practices. Amajority of the mothers were having a lower level of autonomy. IYCF practices were found to be poorer among the female children and those delivered by Caesarean Section. Moderately positive correlation was found between mothers' autonomy and IYCF practices.